Diffusion Tensor MRI to Assess Damage in Healthy and Dystrophic Skeletal Muscle after Lengthening Contractions. (15th November 2011) - McMillan, Alan B.; Shi, Da; Pratt, Stephen J. P.; Lovering, Richard M.
Abstract : The purpose of this study was to determine if variables calculated from diffusion tensor imaging (DTI) would serve as a reliable marker of damage after a muscle strain injury in dystrophic ( mdx ) and wild type (WT) mice. Unilateral injury to the tibialis anterior muscle (TA) was induced in vivo by 10 maximal lengthening contractions. High resolution T1- and T2-weighted structural MRI, including T2 mapping and spin echo DTI was acquired on a 7T small animal MRI system. Injury was confirmed by a significant loss of isometric torque (85% in mdx versus 42% in WT). Greater increases in apparent diffusion coefficient (ADC), axial, and radial diffusivity (AD and RD) of the injured muscle were present in the mdx mice versus controls. These changes were paralleled by decreases in fractional anisotropy (FA). Additionally, T2 was increased in the mdx mice, but the spatial extent of the changes was less than those in the DTI parameters. The data suggest that DTI is an accurate indicator of muscle injury, even at early time points where the MR signal changes are dominated by local edema.